The Role of The Lecturer In Forming Students' Islamic Character - Mardiah Astuti; Herlina Herlina; Tsania Khairana; Nike Asalliyah Saputrie; Intan Yolanda (Journal Analytica Islamica, 2023)
This research aims to determine the importance of the role of lecturers in shaping the character of students at the State Islamic University Raden Fatah Palembang. The type of research used is qualitative, with a descriptive approach. Data collection techniques include interviews, observations, and documentation. The results obtained indicate that lecturers play a significant role in how students develop Islamic character in the MPI study program at UIN Raden Fatah Palembang, both as role models, inspirations, motivators, and evaluators in the process of forming students' Islamic character. Supporting factors include campus policies, understanding of values, care, and a good environment. Meanwhile, inhibiting factors include the need for increased awareness among both lecturers and students regarding the importance of students' Islamic character.Penelitian ini bertujuan untuk mengetahui seberapa penting peran dosen dalam membentuk karakter mahasiswa di Universitas Islam Negeri Raden Fatah Palembang. Jenis penelitian yang digunnakan adalah kualitatif, dengan pendekatan deskriptif. Teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Hasil yang diperoleh bahwa pengajar memiliki peran yang besar terhadap bagaimana mahasiswa mengembangkan karakter Islami mahasiswa Prodi MPI UIN Raden Fatah Palembang, baik sebagai teladan, sebagai inspirasi dan motivator juga sebagai evaluator dalam proses pembentukan karakter Islami mahasiswa. Faktor pendukungnya yakni kebijakan kampus, pemahaman nilai, kepedulian dan lingkungan yang baik. Sedangkan faktor penghambatnya yakni perlu adanya peningkatan kepedulian baik bagi dosen juga mahasiswa terhadap pentingnya karakter Islami mahasiswa.